IMPLEMENTING MIXED LAND USE ROOTING JANE JACOBS’ CONCEPT OF DIVERSITY IN URBAN SUSTAINABILITY - bramiana, chely novia; Widiastuti, Ratih; Harsritanto, Bangun IR (architecture department, Engineering faculty, Universitas Diponegoro, 2017)
nowadays, sustainability has become an important issue in any development project, including area development. Thishappen because the area development requires space, in this case land. As people developing land, it damages theenvironment. It means there will be less balance between built environment and natural environment. This calls forconcern in urban sustainability. One of the ways to restore the balance is to reduce as much land as possible to be builtby maximizing the space. This paper will explore the multiple space use in terms of mixed-use development in differentlevel and also assess mixed land use implementation, which include the concept of diversity in urban sustainability